PEMAKZULAN IMRAN KHAN SEBAGAI UPAYA MEMPERTAHANKAN DOMINASI DINASTI BHUTTO DAN SHARIF DI PAKISTAN TAHUN 2022 - Pratama, Naufal Arief; Kartini, Evida (BHUVANA: Journal of Global Studies, 2025)
This study aims to analyze how the impeachment of Imran Khan in 2022 was part of an effort to maintain the political dominance of the Bhutto and Sharif dynasties in Pakistan. Imran Khan's victory in the 2018 general election marked a shift in Pakistan’s political power, which had long been dominated by the Bhutto and Sharif families through the Pakistan People’s Party (PPP) and the Pakistan Muslim League-Nawaz (PML-N). Khan’s success in challenging the dominance of these two dynasties was perceived as a threat to their political existence and long-standing popularity. This research employs a qualitative method with secondary data analysis, including a literature review from various relevant sources, which is then examined through the lens of cartel party theory and the concept of inter-party cooperation. The findings indicate that Imran Khan’s impeachment was an effort by the Bhutto and Sharif dynasties in Pakistan. Both dynasties played a significant role, from the formation of the coalition and consolidation of power to exerting political and legal pressure on Khan. These efforts were aimed at eliminating Khan from the political stage in Pakistan and ensuring he would not pose a threat in the future.